1989
DOI: 10.1007/bf00558128
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of caerulein-induced gall bladder emptying by cimetropium bromide in humans

Abstract: The effect of cimetropium bromide, a new potent antimuscarinic compound, on caerulein-induced gall bladder emptying in 8 male volunteers was studied by real time ultrasonography. During saline infusion, caerulein (10-40 ng.kg-1.h-1) induced dose-dependent emptying of the gall bladder. There was a significant linear correlation between the dose of the peptide and the reduction in gall bladder size. A continuous infusion of cimetropium bromide (5 mg.h-1) significantly inhibited the contracting effect of caerulei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In humans, it reduces the motor responses of the colon to eating [10,11], shortens intestinal transit time in patients with irritable bowel syndrome [18] and delays fatty meal-and cerulein-induced gallbladder emptying [7,19,20], No data are available from these studies on duration of action and potency in comparison to other drugs. The present study found that cimetro pium and atropine had a similar maximal inhibitory activity on esophageal motility, though the duration of the effect was shorter (less than 60 min) for cimetropium.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it reduces the motor responses of the colon to eating [10,11], shortens intestinal transit time in patients with irritable bowel syndrome [18] and delays fatty meal-and cerulein-induced gallbladder emptying [7,19,20], No data are available from these studies on duration of action and potency in comparison to other drugs. The present study found that cimetro pium and atropine had a similar maximal inhibitory activity on esophageal motility, though the duration of the effect was shorter (less than 60 min) for cimetropium.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the test meal was as follows: fat 8.2 g (41 %), protein 2.2 g (1 1 %) and carbohydrate 9 .6 g (48%). The choice of cerulcin doses was based on previous studies from our laboratory showing that 10 ng/kg/h is the lowest dose capable of significantly contracting the gallbladder and that the dose of 40 ng/kg/h causes an almost complete contraction o f this organ [ 14], On the other day, neuro tensin (Peninsula Laboratories Europe Ltd., Mersey side. UK.)…”
Section: Methodsmentioning
confidence: 99%